Effect of in ovo injection of some B-group vitamins on performance of broiler breeders and their progeny. Issue 1 (2nd January 2022) - Tufarelli, Vincenzo; Ghane, Farhad; Shahbazi, Hossein Reza; Slozhenkina, Marina; Gorlov, Ivan; Viktoronova, Frolova Maria; Seidavi, Alireza; Laudadio, Vito
SUMMARY: Many researchers around the world have been attracted by the delivery of various nutrients, supplements, safety factors, vaccines and drugs through in ovo injection to enhance the production performance, immunity and health of broilers. The purpose of this review is to summarise the information on in ovo injection of some B-group vitamins into the eggs of broiler breeder flocks and their progeny. The available results of different trials showed that in ovo injection of thiamine as well as riboflavin at 100 μg concentration improved hatching, conversion factor and body weight in broilers. It improved the chickens' performance and other performance indices such as conversion coefficient, one-day weight and body weight, and also had a positive effect on the immunity (such as increasing IgM and IgG levels and increasing lysozyme activity) of experimental treatments. On the other hand, in ovo injection of choline did not affect the hatchability rate, but improved the performance indices of the experimental treatments, as well as the effect found with in ovo injection of folic acid. In ovo injection of 40–100 μg of folic acid had no effect on hatchability rate, but had significant effects on the immune system (increasing IgM and IgG levels, and increasing lysozyme activity, and increasing lymph node weight in experimental treatments) and performance. In addition, in ovo injection of pyridoxine at a concentration of 100 μg as well as cobalamin at 40 μg improved the hatchability and performance indices (feed conversion ratio, body weight). Furthermore, in this review, we attempt to provide a comprehensive overview of this issue by outlining the reports and explaining the mechanism of action of these vitamins.